Measuring social return on investment of research projects on Thai functional fruits, fruit trees, and fruit products: A comprehensive study - Kongmanee, Chaiya; Ahmed, Ferdoushi; Prommee, Paratta; Longpichai, Onanong (Asian Journal of Agriculture and Rural Development, 2025)
The Thailand Research Fund (TRF) paid for a total of 12 research projects on Thai fruits and fruit products. The studies looked at and measured the social return on investment (SROI). The fruits studied included functional fruits like mango, pomelo, papaya, and banana. We collected the data through structured questionnaires and in-depth interviews with the key informants of the 12 research projects. We employed the SROI analysis tool to analyze the data. The value of the net benefit of the research projects in terms of output and outcome was estimated to be 125,389,794 THB (Thai Baht), while the Thailand Research Fund (TRF)’s research funding for these projects amounted to 11,883,370 THB. Therefore, the SROI of the projects is estimated to be 10.55. This value implies that the TRF was able to achieve an SROI of 10.55 THB for each 1.0 THB investment in the research projects. The findings suggest that TRF’s investment in the research projects on Thai functional fruits and fruit products was successful and effective as well as worth value. The study findings might be beneficial for TRF, research grant associations, and educational institutions to formulate appropriate policies for further research support.